MRI findings of pancreatic intraductal oncocytic papillary neoplasm: three case reports and review of literature - Xiang, Yunan; Chen, Xiaojun; Zhan, Xiafei; Yan, Zhihan; Pan, Jiangfeng; Wang, Xinyu (Frontiers in Medicine, 2025)
BackgroundPancreatic intraductal oncocytic papillary neoplasms (IOPNs) are uncommon precancerous lesions frequently mistaken for other tumors because of their similar imaging characteristics. The concept of IOPN was first proposed by Adsay et al. in 1996. Recently, an increasing number of reviews on IOPN have been published, however, literature focusing on its imaging features remains scarce. This study retrospectively analyzed the clinical, imaging, and pathological data of three patients with pathologically confirmed pancreatic IOPN, alongside a review of the latest findings in relevant literature.Case presentationWe described three cases of IOPN in elderly patients, with a male-to-female ratio of 1:2. Among these cases, only one patient exhibited abdominal pain, while the other two were asymptomatic. MRI revealed clearly defined mixed-signal masses in the pancreatic head or tail in each case, with the solid components showing moderate enhancement progressively on contrast imaging. After undergoing surgical treatment, all three patients showed no significant clinical symptoms or recurrence signs during follow-up evaluations over 4–6 months.ConclusionOur article provides preliminary evidence of MRI characteristics in pancreatic IOPN, which are essential for understanding its imaging features and aiding in differential diagnosis.